Recovery of physical activity after cesarean delivery and its relationship with pain. Issue 10 (October 2019) - Sharpe, Emily E.; Booth, Jessica L.; Houle, Timothy T.; Pan, Peter H.; Harris, Lynnette C.; Aschenbrenner, Carol A.; Eisenach, James C.
Abstract : Abstract: Pain and physical activity are tightly intertwined. Although their relationship has been explored in chronic pain conditions, we know little about the pattern of recovery in activity and its short- and long-term relationship with pain after surgery. We recruited 103 women undergoing elective cesarean delivery and acquired daily pain assessments and hourly steps in 98 of them for 2 months after surgery. Compliance was good, with 78% of subjects missing less than 7 days of activity. Study personnel required daily checking for compliance and 20 minutes per subject per week in study. Activity increased over the first 2 postoperative months in a log(time) manner. The slope of each modeled individual curve for activity was inversely correlated ( r = −0.54; P < 0.0001) with worst daily pain. After removing these 2-month trends, pain and activity within an individual day were negatively associated with each point increase in pain being inversely associated with −119 steps (95% confidence interval [CI] = −214 to −25; P = 0.013). A patient's previous experience of pain was not associated with current activity as well as current activity was not associated with future pain scores. These data, although limited by the study of a single operation in a unique social circumstance with low risk of chronic postsurgical pain, demonstrate feasibility of measuring hourly activity for 2 months after surgery. Recovery from pain and inactivity are tightly correlated, and the negative relationship between within-day pain and activity without interday carryover relationships is in stark contrast to findings in chronic pain conditions. Abstract : Daily steps after cesarean delivery increases in a log(time) manner with a slope that is inversely correlated with worst daily pain.